PENERAPAN METODE HYBRID SSA-ARIMA PADA PERAMALAN INDEKS HARGA KEBUTUHAN PERTANIAN YANG DIBAYAR PETANI DI PROVINSI SULAWESI SELATAN: indonesia - Fahmuddin S, Muhammad; Ruliana; Muh. Imam Shadiq (Program Studi Statistika Fakultas MIPA UNM, 2025)
This study aims to determine the results and accuracy of forecasting the farmer's price index (IHDP) in South Sulawesi Province using Hybrid SSA-ARIMA. Hybrid SSA-ARIMA is a combination of two good time series methods to improve forecasting accuracy, especially for IHDP data that contains trend and seasonal elements. The data used is the South Sulawesi IHDP data from January 2019 to June 2024 which is sourced from the official website of the Central Statistics Agency. The results of the IHDP forecast in South Sulawesi for the next 12 months from July 2023 to June 2024 tend to increase with the largest increase in September 2024 of 1.184 with a forecast accuracy based on the Mean Absolute Percentage Error (MAPE) of 1.59%. This shows that Hybrid SSA-ARIMA has very good forecasting capabilities